Thyroid Storm Triggered by Partial Hydatidiform Mole: A Rare and Life-Threatening Complication - Hailey Cox; Maggie Wong; Jena Preszler; Nikolina Docheva; Nauman Khurshid (American Journal of Perinatology Reports)
A 26-year-old woman, gravida 1 para 0 at 14 weeks' 1-day gestation, presented with vaginal spotting and systemic symptoms, including palpitations, shortness of breath, heat intolerance, nausea, and vomiting for 2 weeks. Workup revealed maternal tachycardia, severe-range blood pressure, elevated beta human chorionic gonadotropin of 2,442,400 mIU/mL, suppressed thyroid stimulating hormone, and elevated T4, consistent with thyroid storm with possible preeclampsia with severe features.1 A transvaginal ultrasound suggested a partial molar pregnancy; this was later confirmed by surgical pathology. This case highlights the rare yet serious complications of hydatidiform mole, in particular, a partial molar pregnancy, including thyroid storm and superimposed preeclampsia, emphasizing the importance of management at a tertiary care center with a multidisciplinary team to optimize maternal outcomes.2 3